Dinamika Psikologis pada Pelaku Pembunuhan Berencana (Study Kasus pada Pelaku Pembunuhan) - Riduan, Riduan; Proborini, Renyep; Sulastri, Sulastri (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
This research aims to investigate and understand the psychological dynamics of perpetrators of premeditated murder, with a focus on a case study detailing the incident on 18 May 2020. This case involves a suspect, who traveled from Pandeglang Regency, Banten, to Lampung Province to celebrate Eid. This tragic event raises questions about the psychological factors that may have contributed to the perpetrator's decision to plan and carry out such violent acts. This research aims to identify and analyze the psychological factors involved in premeditated murder cases, provide further understanding of the perpetrator's motivation, and explore the impact on the victim and the surrounding environment. This research uses a descriptive qualitative approach with case study analysis. Data was collected through interviews with related parties, document analysis, and chronological reconstruction of events based on witness statements. In-depth analysis reveals that the psychological dynamics of perpetrators of premeditated murder involve factors of interpersonal conflict, trauma experiences, and lack of social support. Conflicts with family members, especially wives, as well as traumatic experiences related to the COVID-19 pandemic and social rejection, form the perpetrator's psychological background. The results of this research provide insight into the complexity of factors that influence perpetrator decisions and their impact on victims and the surrounding community.